JSPS-6 Influenza D virus and bovine coronavirus play important roles in bovine respiratory disease in Japan - Hirohisa Mekata (Hemera Zoa, 2018)
Bovine respiratory disease (BRD) is one of the most commonly diagnosed causes of morbidity and mortality in the cattle industry. Co-infection with several viruses and bacteria causes BRD. Despite the use of antibiotics and several commercial vaccines against viruses, such as bovine respiratory syncytial virus (BRSV), bovine viral diarrhea virus (BVDV) 1 and 2, bovine herpesvirus 1, bovine adenovirus 7 and bovine parainfluenza virus 3, BRD remains the most common and costly problem in Japan. Therefore, we suspect that viruses not treated by the vaccines are a possible cause of BRD.Metagenomic analysis has recently allowed comprehensive viral characterization of the bovine respiratory tract. Ng et al. reported that bovine adenovirus 3, bovine rhinitis A virus and influenza D (FluD) virus were significantly associated with BRD in the USA [1]. Mitra et al. reported that FluD virus was significantly associated with respiratory disease, and viruses that are commonly associated with BRD, such as BVDV, bovine herpesvirus 1, BRSV, and bovine parainfluenza virus were detected less frequently in Mexico and the USA [2]. Although the viral pathologies and clinical diseases in sole infection appear mild, these results suggest that they play an essential role as a trigger of BRD.To identify which viruses were associated with BRD in Japan, we first performed a viral metagenomic analysis using nasal swab samples from respiratory-diseased cattle. The results suggested that bovine coronavirus (BCoV) and FluD virus played a significant role. Therefore, we conducted a molecular-epidemiological survey of nasal swab samples from respiratory-diseased and healthy cattle to assess the contribution of BCoV and FluD virus. Finally, we performed a phylogenetic analysis and assessed the antigenicity.